Electrode Placement Affects Clinical Outcome in Transcutaneous Electrical Nerve Stimulation for Knee Osteoarthritis: A Combined Cadaver Study and Randomized Controlled Trial - Yu Xu; Yanfu Bai; Meimin Deng; Xuyi Hu; Manqin Lian; Zhisheng Huang; Lingling Su (Pain and Therapy)
Abstract Introduction Transcutaneous electrical nerve stimulation (TENS) is a widely used physical therapy for knee osteoarthritis (OA) pain management. However, the optimal electrode placement for TENS in knee OA remains unclear. Given that TENS delivers stimulation via electrodes to cutaneous nerves, placing electrodes in areas with high nerve density should be the precondition to exert its therapeutic effects. However, high-density nerve areas around the knee and corresponding electrode placement strategies have yet to be investigated. Methods An anatomic study was conducted on 20 adult formalin-fixed cadavers to identify the high-density nerve areas around the knee. Then, to standardize electrode placement, the patellar width was used as a reference to determine distances from the patellar borders. Subsequently, 80 patients with Kellgren–Lawrence grade 2 or 3 knee OA were enrolled in a randomized, double-blinded trial. Participants received TENS therapy with electrodes placed either on the identified high-density nerve areas (study cohort, n = 40) or on traditional pain areas (control cohort, n = 40). Results Four high-density nerve areas were identified: the quadriceps tendon, patellar ligament, medial joint line area, and superior medial area of the knee. Over the follow-up period, patients in the study cohort showed significantly greater improvements in VAS score and WOMAC index total score, as well as in pain, stiffness, and function subscales compared with those in the control cohort (all P < 0.05). Conclusions These findings suggest that positioning electrodes over high-density nerve areas allows TENS more effectively activate sensory afferents, thereby enhancing pain relief. Trial Registration Chinese Clinical Trial Registry identifier, ChiCTR2500098200, 4 March 2025, retrospectively registered.